2016
DOI: 10.1146/annurev-virology-110615-042238
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Biology of Hepatitis B Virus: Form and Function

Abstract: Hepatitis B virus is one of the smallest human pathogens, encoded by a 3,200-bp genome with only four open reading frames. Yet the virus shows a remarkable diversity in structural features, often with the same proteins adopting several conformations. In part, this is the parsimony of viruses, where a minimal number of proteins perform a wide variety of functions. However, a more important theme is that weak interactions between components as well as components with multiple conformations that have similar stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
138
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 178 publications
(246 reference statements)
5
138
0
1
Order By: Relevance
“…Single particle analysis revealed that, in these conditions, MS2 phage could assemble its capsid in both T = 3 and T = 4 icosahedral settings, as well as poorly defined hybrids of these two architectures. The formation of icosahedral capsids with different triangulation numbers has been previously reported for other viruses (Venkatakrishnan and Zlotnick, 2016;Jung et al, 2019), which is not wholly unexpected considering the close symmetry relationships between related icosahedral triangulations (Prasad and Schmid, 2012).…”
Section: A B D Csupporting
confidence: 69%
“…Single particle analysis revealed that, in these conditions, MS2 phage could assemble its capsid in both T = 3 and T = 4 icosahedral settings, as well as poorly defined hybrids of these two architectures. The formation of icosahedral capsids with different triangulation numbers has been previously reported for other viruses (Venkatakrishnan and Zlotnick, 2016;Jung et al, 2019), which is not wholly unexpected considering the close symmetry relationships between related icosahedral triangulations (Prasad and Schmid, 2012).…”
Section: A B D Csupporting
confidence: 69%
“…The recombinant version of the HBV e antigen used to solve the structure was Cp(‐10)149, and the C‐terminal sequence was based on earlier work . This was also consistent with the HBcAg construct Cp149 used for many structural studies . More recent work shows that HBeAg C‐terminal processing occurs in the Golgi apparatus by the transmembrane protein convertase furin.…”
Section: Discussionsupporting
confidence: 81%
“…The assembly of HBcAc VLPs also induces changes in mean hydrophobicity around aromatic amino acids as capsid assembly relies on hydrophobic interaction forces (Venkatakrishnan & Zlotnick, 2016;Wynne et al, 1999). Tyrosine-132 is especially important for the assembly (Bourne, Katen, Fulz, Packianathan, & Zlotnick, 2009).…”
mentioning
confidence: 99%